Structure of the periplasmic domain of SflA involved in spatial regulation of the flagellar biogenesis of Vibrio reveals a TPR/SLR-like fold. (15th April 2019) - Sakuma, Mayuko; Nishikawa, Shoji; Inaba, Satoshi; Nishigaki, Takehiko; Kojima, Seiji; Homma, Michio; Imada, Katsumi
Abstract: Bacteria have evolved various types of flagellum, an organella for bacterial motility, to adapt to their habitat environments. The number and the spatial arrangement of the flagellum are precisely controlled to optimize performance of each type of the flagellar system. Vibrio alginolyticus has a single sheathed flagellum at the cell pole for swimming. SflA is a regulator protein to prevent peritrichous formation of the sheathed flagellum, and consists of an N-terminal periplasmic region, a transmembrane helix, and a C-terminal cytoplasmic region. Whereas the cytoplasmic region has been characterized to be essential for inhibition of the peritrichous growth, the role of the N-terminal region is still unclear. We here determined the structure of the N-terminal periplasmic region of SflA (SflAN ) at 1.9-Å resolution. The core of SflAN forms a domain-swapped dimer with tetratricopeptide repeat (TPR)/Sel1-like repeat (SLR) motif, which is often found in the domains responsible for protein–protein interaction in various proteins. The structural similarity and the following mutational analysis based on the structure suggest that SflA binds to unknown partner protein by SflAN and the binding signal is important for the precise control of the SflA function.